Pogoji za inkluzijo v vzgoji in izobraževanju po oceni ravnateljev - Kovač, Janez; Ščuka, Tanja; Čagran, Branka (Revija za elementarno izobraževanje, 2017)
Conditions for Inclusive Education from the Viewpoint of Headteachers. The paper presents conditions for inclusive education as perceived by headteachers in Slovenian basic schools. In the theoretical part, we focused on the key elements of inclusive schools, i.e. headteachers, teachers, and parents of children with special needs. In conclusion, we briefly highlight some theoretical propositions in relation to additional professional support in basic schools. In the empirical part of the paper, we present the results of an online survey conducted among headteachers in Slovenian basic schools. The aim of the survey was, among other things, to find how headteachers perceive conditions for inclusive education – those relating to headteachers themselves, to teachers/professional staff working with students with special needs, and those relating to school as a whole. Here, we also paid our attention to differences regarding the number of children with special needs who are included in regular programme with adjusted implementation and additional professional assistance. The obtained results provide an opportunity for assessment of current situation, and for further consideration concerning the development of inclusive education in Slovenia in the future.